2018
DOI: 10.18632/oncotarget.25251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different mutational profiles in cancers arising in specific colon segments by next generation sequencing

Abstract: The objective of this study was to investigate the mutational profiles of cancers arising in different colon segments. To this aim, we have analyzed 37 colon cancer samples by use of the Ion AmpliSeq™ Comprehensive Cancer Panel. Overall, we have found 307 mutated genes, most of which already implicated in the development of colon cancer. Among these, 15 genes were mutated in tumors originating in all six colon segments and were defined “common genes” (i.e. APC, PIK3CA, TP53) whereas 13 genes were preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The frequency of those mutations increased from the colitis to nally the CRC, so they could be used as predictors for disease progression. Most of the above identi ed somatic mutations were observed mostly with the CRC [47], except for (c.640delT in ATM), (c.1621A > C in KIT), (c.2071G > A in RET) & (c.121delG in TP53) which were observed respectively in breast [57], soft tissues [58] & head and neck cancers [59]. This is the rst study to report their association with the colorectal carcinogenesis in Egyptian CRC patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The frequency of those mutations increased from the colitis to nally the CRC, so they could be used as predictors for disease progression. Most of the above identi ed somatic mutations were observed mostly with the CRC [47], except for (c.640delT in ATM), (c.1621A > C in KIT), (c.2071G > A in RET) & (c.121delG in TP53) which were observed respectively in breast [57], soft tissues [58] & head and neck cancers [59]. This is the rst study to report their association with the colorectal carcinogenesis in Egyptian CRC patients.…”
Section: Discussionmentioning
confidence: 74%
“…The present study reported two somatic mutations with functional loss in FBXW7 gene (c.2001delG & c.4900A > G). These mutations were previously reported to be found mainly in the CRC patients [47,34]. Moreover, a recent study reported the presence of an association between the FBXW7 mutations and resistance to anti-epidermal growth factor receptor (EGFR) immunotherapy treatment that commonly used to manage metastatic CRC [48].…”
Section: Discussionmentioning
confidence: 97%
“…The association of rectal tumors with inferior PFS was surprising, considering that PFS in rectal tumor patients treated with bevacizumab and chemotherapy has been reported to be longer than for most other tumor sites [ 44 ]. Regarding tumor sites, it has further been reported that splenic flexure tumors have a high proportion of PTPRD mutations [ 45 ]. Although it is possible that patients with specific tumor locations are more likely to harbor PTPRD mutations and could be more likely to be bevacizumab resistant, our cohort only included two patients with splenic flexure tumors, and was therefore not suitable to confirm those results.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, high expression of SMUG1 is associated with favorable prognosis in ovarian cancer [ 47 ]. Additionally, low SMUG1 expression and mutations in SMUG1 are associated with poor prognosis in breast and colon cancer, respectively [ 48 , 49 ]. Abdel-Fatah and colleagues looked at SMUG1 mRNA or protein expression levels in triple negative breast cancer cells.…”
Section: Smug1 and Cancermentioning
confidence: 99%